(untitled) (Research, Society and Development, 2022)
In this article, we bring the results of an investigation that sought to verify how the questionnaires applied for data collection, carried out over three years with high school students, have been set as an incentive to enter the metacognitive system in the process of learning in physics. The proposed instrument for data collection was made up of four questionnaires: “Self-assessment” (Q1); “After evaluation” (Q2); “Metacognitive inventory” (Q3); and “Final questionnaire” (Q4). Analyzing the students’ answers, it was concluded that the Q1 questionnaires were instruments of metacognitive incentive that provided insertion to the process through the metacognitive reflection that was the trigger to access metacognitive knowledge, both self-knowledge and manifestations of metacognitive experience. With Q2 and Q3 questionnaires, it was possible to signal that these have also worked as na incentive at entering the metacognitive system, possibly through activation at times, of the procedural metacognitive knowledge. The Q4 questionnaire identified metacognitive knowledge, in which the student triggers the memories of the process of taking awareness of the conditions in which the used strategies affected learning.